The Effect of Digital Literation, Internationalization, and Learning Orientation on The Quality of Learning Through Self Direct Learning as Variables Moderating - Astuti, Dwi Puji; Kardiyem, Kardiyem; Rachmadani, Wulan Suci; Widia, Syam (Universitas Negeri Semarang, 2021)
This study aims to determine the effect of digital literacy, internationalization, learning orientation on the quality of learning, and the role of the self-direct learning variable as a moderating variable. The population in this study were students of accounting education class 2016-2019. Samples were taken by purposive sampling as many as 75 students. The data collection technique used a questionnaire. Data analysis was performed using the classical assumption test with the IBM SPSS Statistic 26 application program. The results showed that digital literacy, internationalization, learning orientation did not affect the quality of learning. However, the existence of the self-direct learning variable as a moderating variable can strengthen the positive and significant influence on the quality of learning. Students must improve their learning orientation and digital literacy associated with improving the quality of learning. Keywords Internationalization; Quality of Learning; Digital Literacy; Learning Orientation; Self Direct-Learning